1982
DOI: 10.3109/15563658208990377
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Activated Charcoal Following Gastric Lavage in Acute Drug Emergencies

Abstract: The efficacy of administering a slurry of 100 g of activated charcoal (AC) via the gastric tube following lavage was assessed in 25 treated and 37 control patients presenting to the emergency room with chemical evidence of sedative-hypnotics or aspirin in the blood. Efficacy was evaluated as the ability of AC to prevent further absorption as determined by subsequent blood drug concentration changes. Although fewer patients in the AC group showed increased blood drug concentrations, the differences were not sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Fifty-six patients (47%) consumed the entire container of AC, which included 46 15-g containers, 8 25-g containers, and 2 30-g containers. Eight (7%) of 116 children who were treated at home vomited after AC administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-six patients (47%) consumed the entire container of AC, which included 46 15-g containers, 8 25-g containers, and 2 30-g containers. Eight (7%) of 116 children who were treated at home vomited after AC administration.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][7][8][9] Since this work has been done, there has been a continuous 10-year decline in the use of ipecac while at the same time a comparable increase in the use of AC. 10 This has followed a similar decline in the general use of home GI decontamination.…”
Section: Discussionmentioning
confidence: 98%
“…Activated charcoal, single-dose There were 13 clinical trials (level 1b) that examined the effect of activated charcoal on aspirin absorption (193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205). None of these studies was performed as out-of-hospital care.…”
Section: Treatment Measuresmentioning
confidence: 99%
“…There was no benefit to the addition of activated charcoal to lavage based on the proportion of patients whose serum salicylate concentrations continued to rise after the intervention. The number of aspirin patients was small and the serum concentrations were low, indicating non-serious poisoning (194). The other 11 clinical studies involved adult volunteers who received non-toxic doses of aspirin prospectively.…”
Section: Treatment Measuresmentioning
confidence: 99%
“…One study found that patients who received GL and activated charcoal did no better than those that received activated charcoal alone [8,9]. In fact, patients that received GL had an increased incidence of aspiration pneumonia despite being endotracheally intubated [9].…”
Section: Introductionmentioning
confidence: 99%